METHODOLOGICAL ESSENCE OF DEVELOPMENT OF STUDENTS' ENTREPRENEURSHIP COMPETENCIES BASED ON VITAGEN EXPERIENCE - Malika Pirniyazova (International Scientific and Current Research Conferences, 2023)
The main “arsenal” in solving the scientific and pedagogical problem is the methodology. Therefore, it is important to form a methodology that serves to find a solution to the chosen problem. The thesis outlines the general essence of the research methodology.